Deteksi Bakteri Indikator Keamanan Pangan Pada Sosis Daging Ayam Di Pasar Flamboyan Pontianak - Ari Hepi Yanti, Emma Kartika, Siti Khotimah (Jurnal Protobiont, 2014)
The sellers in Flamboyan market Pontianak sell the sausages without freezing box. This could trigger the growth of pathogen bacteria on the sausages. The aims of this research was to know the safety level of chicken sausages in Flamboyan market based on the amount of Coliform, Escherichia coli, Staphylococcus aureus and Salmonella sp. Samples of chicken sausages were randomly taken from 4 sellers as many as 12 packs. The samples were kept in room temperature (28C-30C) for 1 day, 3 days and 5 days. The amount of bacteria was calculated by using Most Probably Number and Total Plate Count methods. The result showed that there were changes on the color, the taste and the texture of chicken sausages at 3rd and 5th day. The number of bacteria from day 1 until day 5 is less than SNI (7388:2009), that was < 1 105 CFU/g. The number of S. aureus and MPN value of Coliform and E. coli from day 1 until day 5 was more than SNI (7388:2009), that was > 1 102 CFU/g, > 10 MPN/g and > 3 MPN/g, respectively. It is also known that chicken sausages positively contained Salmonella sp. in every 25g samples.